Literasi Fintech, Kompetensi Digital, dan Minat Karir Auditor Digital: Pendekatan Theory of Planned Behavior pada Mahasiswa Akuntansi - Jumriaty Jusman; Masrahati Masrahati; Ikhsan Purnama; Ahmad Nouruzzaman (Politeknik Ganesha Medan, 2026)
The rapid digitalization of the accounting and auditing profession has increased demand for digitally skilled auditors, particularly those capable of operating in FinTech-driven environments. This study examines the simultaneous and partial effects of FinTech literacy and digital competency on students’ interest in pursuing a career as a digital auditor, drawing on the Theory of Planned Behavior (TPB) as the underlying theoretical framework. Using a quantitative approach, data were collected from undergraduate accounting students and analyzed using multiple linear regression with SPSS. The results of the F-test indicate that FinTech literacy and digital competency jointly have a significant effect on students’ interest in the digital auditor profession. However, partial testing reveals that both FinTech literacy and digital competency exhibit a negative and significant individual effect on career interest. These findings suggest that higher levels of knowledge and digital skills may simultaneously increase awareness of professional risks, technological complexity, and job demands associated with digital auditing, which in turn can reduce career interest. The results align with TPB by indicating that perceived behavioral control and attitude toward the profession may be shaped not only by competence but also by perceived difficulty and risk. This study contributes to the literature by highlighting the paradoxical role of digital competence and FinTech literacy in career intention formation and provides practical implications for accounting education in designing curricula that balance skill development with career orientation and risk awareness. This study contributes to the literature on digital audit career intentions by demonstrating that advanced digital capabilities may generate ambivalent effects on career interest, particularly through heightened risk perception and job demands. From a practical perspective, the findings imply that accounting curricula and audit education should not only strengthen digital and FinTech competencies but also address career orientation, professional readiness, and realistic perceptions of digital audit work.